IMPROVED CHEMISTRY LEARNING OUTCOMES THROUGH THE JIGSAW COOPERATIVE LEARNING MODEL IN VOCATIONAL SCHOOL - Ahmad, Fandi; Sari, Nur Indah; Hatta, A. Afrinaramadhani; Amaliah, Rezeki (MACCA : Science-Edu Journal, 2024)
This study aims to improve the chemistry learning outcomes of grade XI students at SMK Jaya Negara Makassar by applying the Jigsaw-type cooperative learning model. This class action research (PTK) was conducted in two cycles, with the research subjects consisting of 20 students of class XI of SMK Jaya Negara Makassar. Each cycle consisted of four stages of activities, namely planning, action implementation, observation, and reflection. Data collection in this study was conducted through observation, tests, and documentation. The data analysis technique used was quantitative analysis, including calculating learning outcome scores, data presentation, and conclusion drawing. The results showed a significant increase in student learning outcomes. The average student score in cycle I was 69.75, while it increased to 86.15 in cycle II. In addition, the percentage of completeness of learning outcomes in cycle I reached 60%, and in cycle II increased to 100%, which showed perfect criteria. Based on this study's results, applying the Jigsaw-type cooperative learning method effectively improves student learning outcomes in chemistry subjects in class XI of SMK Jaya Negara. This research is expected to positively contribute to learning practices in schools and become a reference for further research on cooperative learning models in chemistry education.